Workshop report on The Phenomenology of Refuge and Belonging: Technical University of Darmstadt, Germany on 4th July 2022. - Bibile, Nayana (HannahArendt.net, 2022)
Refuge and belonging are lived conditions that have always carried great significance and require greater attention than ever. In vexed contexts of populisms and ever hardening national borders that have given impetus to embolden a visible and vocal rightwing politics, it is therefore critical to rethink how refuge manifests. Indeed, these developments demonstrate in a rather blunt manner the danger of objectification of refuge and notions of belonging. Hence, this workshop was an attempt to radically rethinkrefuge and move beyond its emergency-centric conception to begin creating narratives to counter this politics through a critical phenomenology and restore the individual to the centre of these problematics and shift the tenor of present debates.